The effect of oil palm trunk and oil palm fruit bunch fibre on the mechanical properties of laterite bricks / Noorsaidi Mahat ... [et al.] - Mahat, Noorsaidi; Husin, Husrul Nizam; Khalil, Natasha; Bohari, Asmah Alia (2012)
The main aim of this study was to compare the physical properties and mechanical properties of Oil Palm Trunk (OPT) fibre and Oil Palm Fruit Bunches (OPFB) fibre reinforced laterite bricks. For comparison purposes, the properties such as dimension, density, water absorption and the compressive strength of both types of bricks were determined. The effects of the incorporation of various amounts of fibres on the above properties were analysed. The tests were carried out according to BS 3921: 1985 for clay bricks.The samples were pressed at the factory Majpadu Bricks Sdn. Bhd., Malaysia and tested at the Material Testing Laboratory, Universiti Teknologi MARA, Shah Alam, Malaysia.The findings of this research were, firstly, the dimension of bricks content with OPFB fibres were less accurate than bricks with OPT fibres. Secondly, the density of bricks with OPFB fibres was higher than the density of bricks with OPT fibres. Thirdly, in compressive strength of the bricks with OPFB fibres was higher than bricks with OPT fibres, with the maximum fibre content identified as 3 percent fibres. Finally, the water absorption of bricks with OPFB fibres was lower than the water absorption of bricks with OPT fibres. It can be concluded that the bricks with OPFB fibres had better physical and mechanical properties than bricks with OPT fibres. OPFB fibres is better for reinforcement in the laterite bricks and properties of the bricks with OPT Fibres were to be improved.